Cyclophilin D regulates the dynamic assembly of mitochondrial ATP synthase into synthasomes. Issue 1 (December 2017) - Beutner, Gisela; Alanzalon, Ryan; Porter, George
Abstract Mitochondrial electron transport is essential for oxidative phosphorylation (OXPHOS). Electron transport chain (ETC) activity generates an electrochemical gradient that is used by the ATP synthase to make ATP. ATP synthase is organized into supramolecular units called synthasomes that increase the efficiency of ATP production, while within ATP synthase is the cyclophilin D (CypD) regulated mitochondrial permeability transition pore (PTP). We investigated whether synthasomes are dynamic structures that respond to metabolic demands and whether CypD regulates this dynamic. Isolated heart mitochondria from wild-type (WT) and CypD knockout (KO) mice were treated to either stimulate OXPHOS or open the PTP. The presence and dynamics of mitochondrial synthasomes were investigated by native electrophoresis, immunoprecipitation, and sucrose density centrifugation. We show that stimulation of OXPHOS, inhibition of the PTP, or deletion of CypD increased high order synthasome assembly. In contrast, OXPHOS inhibition or PTP opening increased synthasome disassembly in WT, but not in CypD KO heart mitochondria. CypD activity also correlated with synthasome assembly in other tissues, such as liver and brain. We conclude that CypD not only regulates the PTP, but also regulates the dynamics of synthasome assembly depending on the bioenergetic state of the mitochondria.